EKSPLORASI ALAT MUSIC OGUNG BATAK TOBA TERHADAP KONSEP GEOMETRI LINGKARAN - purba, rIcky rikardo (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2024)
This article delves into the profound meanings and symbolism of the traditional musical instrument Ogung in Batak Toba culture, particularly in the context of the concept of circular geometry. Ogung, a round and flat gong, serves not only as a musical instrument but also reflects greatness, balance, and the cycle of life in Batak Toba tradition. The concept of circular geometry is manifested in the physical form of Ogung, creating a profound connection between artistic form, philosophical values, and traditional art performances. This exploration invites readers to understand how the circle on Ogung not only resonates with harmonic melodies but also conveys a deep message about the unity of humans with nature and the local wisdom embedded in traditional art. Keywords: Exploration,traditional musical instrument , concept of circular geometry